2009
DOI: 10.1510/icvts.2009.208371
|View full text |Cite
|
Sign up to set email alerts
|

Death in low-risk cardiac surgery: the failure to achieve a satisfactory cardiac outcome (FIASCO) study

Abstract: Death in low-risk patients is not studied as frequently as it is in other cardiac patients. We, therefore, sought to determine why some low-risk patients die after cardiac surgery. All low-risk patients (EuroSCORE Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 11 publications
0
27
0
Order By: Relevance
“…In the FIASCO studies, we and others have shown that it is possible to identify factors associated with death in low-risk cardiac surgery patients and that modifying such factors can result in a reduction of avoidable mortality. [6][7][8] The aim of the current study was to look into the mechanism of coronary ostial compromise during AVR in the hope that understanding the prevalence and mechanisms of this complication may help future prevention of such unwanted events. Coronary ostial compromise in AVR is a rare but real problem.…”
Section: Discussionmentioning
confidence: 99%
“…In the FIASCO studies, we and others have shown that it is possible to identify factors associated with death in low-risk cardiac surgery patients and that modifying such factors can result in a reduction of avoidable mortality. [6][7][8] The aim of the current study was to look into the mechanism of coronary ostial compromise during AVR in the hope that understanding the prevalence and mechanisms of this complication may help future prevention of such unwanted events. Coronary ostial compromise in AVR is a rare but real problem.…”
Section: Discussionmentioning
confidence: 99%
“…Perioperative death in low-risk patients is uncommon and had not been thoroughly studied until recently [3][4][5][6][7]. Previous studies defined low--risk with a logistic EuroSCORE ≤ 2 or an additive EuroSCORE ≤ 3, and investigated whether death could be considered preventable due to a technical or system error.…”
Section: Discussionmentioning
confidence: 99%
“…Although the observed in-hospital mortality in very low-risk patients was 0.93%, the expected risk based on the EuroSCORE II was even lower (0.70), and this difference could reach statistical significance in a larger sample. Table 3 summarizes the findings of different studies analyzing death in low-risk patients and virtually 3 of them (from United Kingdom [3,4] and Sweden [5]) showed mortality rates well below 1%. The remaining 2 studies from Turkey reported similar results to ours, though they only included coronary artery bypass grafting that has a well-known lower risk of operative mortality than other types of open heart surgery [6,7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations